Angiotensin Ⅱ type 1 receptor autoantibody-AT1R-Bmal1 axis promotes phenotypic transition of vascular smooth muscle cells and vascular fibrosis - XUE Lingxia; LONG Yaolin; FENG Jiayan (陆军军医大学学报)
‍Objective‍　‍To investigate the mechanism by which angiotensin Ⅱ type 1 receptor autoantibody (AT1-AA) promotes phenotypic switch of vascular smooth muscle cells (VSMCs) and vascular fibrosis through abnormal expression of circadian clock protein BMAL1. Methods‍　‍Twelve male SD rats (6~8 weeks old, weighing 180~220 g) were randomly divided into (n=6) a control group and an AT1-AA-positive group [established by active immunization of SD rats with AT1R extracellular loop Ⅱ peptide (AT1R-ECLⅡ)]. HE and Masson stainings were used to observe structural changes and fibrosis in the thoracic aorta (n=3). Western blotting was performed to detect the expression of Collagen I, phenotypic switch-related proteins (SM22, α-SMA, OPN and MMP2) in vascular tissues and primary VSMCs (n=4), as well as the expression of BMAL1 at CT0, CT4, CT8, CT12, CT16, and CT20. Transwell and scratch assays were used to assess the proliferation and migration of VSMCs (n=3). si-RNA was employed to knock down Bmal1, followed by detection of BMAL1, Collagen I, and phenotypic conversion-related protein expression (n=3). Additionally, AT1-AA-positive AT1R-knockout (AT1R-KO) rats were constructed to measure BMAL1 expression in thoracic aortic tissues (n=4). Results‍　‍The AT1-AA-positive rats had significantly thickened thoracic aortic vessel wall [(140±9)% vs (120±5)%, P<0.05], badly arranged VSMCs, obvious blue Masson staining, and up-regulated Collagen I expression (P<0.05). In the thoracic aorta of AT1-AA-positive rats and AT1-AA-treated VSMCs, the expression of contractile phenotype-related proteins (α-SMA, SM22) was decreased (P<0.05), while the expression of synthetic phenotype-related proteins (OPN, MMP2) was increased (P<0.05). AT1-AA enhanced the scratch healing ability and migration ability of VSMCs. Furthermore, both mRNA and protein levels of Bmal1 were significantly up-regulated at CT12 (P<0.05), and the rhythmicity of Bmal1 was lost. Knockdown of Bmal1 partially ameliorated AT1-AA-induced phenotypic switch of VSMCs. Compared with AT1-AA-positive WT rats, AT1-AA-positive AT1R-KO rats showed significantly reduced BMAL1 expression in the thoracic aorta (1.35±0.06 vs 0.86±0.07，P<0.001). At the cellular level, AT1-AA-induced phenotypic switch and high Collagen I expression in VSMCs were partially improved in AT1R-KO VSMCs. Conclusion‍　‍AT1-AA promotes VSMCs phenotypic conversion and vascular fibrosis through the AT1R-Bmal1 axis.